The Cultural Meaning Of Du’a Hale Folklore In Natakoli Village, Mapitara District, Sikka Regency - Bergita Bei; Antonius M. K. Naro; Rikardus Nasa (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The purpose of this study is to tell the folklore of Dua Hale and the meaning contained therein in Natakoli village, Mapitara district, Sikka regancy.The researcher used qualitative method. Data collection techniques used in this research are observation, interview and documentation.Based on the results of the study, Dua Hale folklore is one of the folklore that is, abandoned and forgotten by the surrounding community. it was found too that cultural meaning in folklore of Dua Hale are: Didactic meanings In folklore the didactic meaning is implied in the form of educational and teaching values society about how to be ethical and etiquette in context social life.There are several meanings implied in the didactic meaning namely: responsibility, willing to sacrifice, courage,and customary law. The historical meaning in folklore, historical meaning is also revealed which is reflected in two parameters general history, namely the time and place contained in the folklore in question. Regarding the time parameter, it is said that folklore takes place in the past and the historical meaning of place names in the story that are still relevant today at the moment, utan welak and hegin and economic meaning. The economic meaning of folklore is reflected in the disclosure or relevant information the economic system of society in which some of the main sources of livelihood are farming and fishing.